Closing the gap: supporting literacy through a computer‐assisted‐reading‐intervention. Issue 1 (28th February 2020) - Vincent, Kerry
Abstract: Schools in England are expected to 'close the gap' for a range of vulnerable pupils who are achieving below the levels seen amongst their same‐aged peers. They are also highly accountable for additional funding that is provided to support this goal. The project reported here involved collating and analysing a range of data in order to evaluate the impact of a widely used computer‐assisted‐reading‐intervention (CARI). Sixteen primary school pupils, all of whom were identified by their school as underachieving in literacy, used the CARI daily over a five‐week period. The post‐intervention data showed some clear gains in reading and spelling skills for all bar one of the children. The findings are discussed in relation to the wider literatures on CARIs. The research concludes that the CARI under investigation offers a useful and cost‐effective adjunct to whole‐class and group reading instruction and may be particularly beneficial for supporting the learning of pupils who are struggling to consolidate the knowledge and skills covered in their regular classroom reading instruction.